2015
DOI: 10.1002/2015ja021463
|View full text |Cite
|
Sign up to set email alerts
|

Hypervelocity dust impacts on the Wind spacecraft: Correlations between Ulysses and Wind interstellar dust detections

Abstract: The Wind spacecraft is positioned just sunward of Earth at the first Lagrange point, while the Ulysses spacecraft orbits above and below the ecliptic plane crossing the ecliptic as far from the Sun as the orbit of Jupiter (∼5 AU). While Wind does not carry a dedicated dust detector, we demonstrate the ability of Wind electric field measurements to detect hypervelocity dust impacts through their impact plasma signatures. Interstellar dust (ISD) and interplanetary dust particles are differentiated based on a yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
5
18
0
Order By: Relevance
“…These dust observed amplitude and polarity of such signals are consistent with voltage induced on the antennas by positive 290 ions produced by impacts on the spacecraft, after it has recollected the electrons (Meyer-Vernet et al 2014); thisnew mechanism explained the previously unexplained voltage sign and amplitude for interstellar dust impacts on Wind, and also the absence of nanodust detection on this spacecraft. The yearly modulation of Wind-observed impacts was found to be consistent with the yearly variation in interplanetary micron dust, Wood et al 2015. Further supporting this conclusion was the observation that both Wind and STEREO observe 295 the same yearly modulation of interstellar dust flux(Kellogg et al 2016).…”
supporting
confidence: 71%
“…These dust observed amplitude and polarity of such signals are consistent with voltage induced on the antennas by positive 290 ions produced by impacts on the spacecraft, after it has recollected the electrons (Meyer-Vernet et al 2014); thisnew mechanism explained the previously unexplained voltage sign and amplitude for interstellar dust impacts on Wind, and also the absence of nanodust detection on this spacecraft. The yearly modulation of Wind-observed impacts was found to be consistent with the yearly variation in interplanetary micron dust, Wood et al 2015. Further supporting this conclusion was the observation that both Wind and STEREO observe 295 the same yearly modulation of interstellar dust flux(Kellogg et al 2016).…”
supporting
confidence: 71%
“…Discontinuities in the RPWS dust density profile are due to gain changes of WBR. The CDA data showed consistent peak densities of around 0.04 m −3 (threshold ∼ 0.8 µm) during the ringgrazing orbits, less than 1 order of magnitude higher than the RPWS dust density, which is within the uncertainty limit of the method (Ye et al, 2014). The density peak measured by RPWS is wider than that by CDA with a full-width halfmaximum of 600-1000 km compared to 475 km for the latter (averaged profile shows a FWHM of 475 km).…”
Section: Cassinimentioning
confidence: 62%
“…The south-polar plume of Enceladus was one of the top discoveries made by the Cassini mission. During the Enceladus plume crossing, besides dust impact signals, RPWS detected plasma oscillations induced by dust impacts, the frequencies of which are equal to the local plasma frequencies (Ye et al, 2014), which can be explained by a beam-plasma instability induced by the impactproduced electrons when their speed exceeds the thermal speed of the ambient plasma (Meyer-Vernet et al, 2017). Comparison of observations (Ye et al, 2014b) showed that the dust density profile measured by RPWS is consistent with that measured by the dedicated dust detector on board.…”
Section: Cassinimentioning
confidence: 99%
“…The flux of the larger dust agrees with measurements of other instruments on different spacecraft and one can distinguish in the data between interstellar and interplanetary dust components (Belheouane et al (2012), Zaslavsky et al (2012), Malaspina et al (2015)). The WIND electric field measurements also were analyzed to derive information on hypervelocity dust impacts, the observed flux variation was found to be in good agreement with measurements from dust detectors, while the direction of the interstellar dust flux could not be directly compared and spacecraft orbits are hugely different (Wood et al (2015)). …”
Section: Interstellar and Interplanetary Dust In The Heliospherementioning
confidence: 99%